ANALISIS KUALITAS DAYA LISTRIK DI PABRIK GULA TRANGKIL PATI DENGAN MENGGUNAKAN SOFTWARE ETAP 12.6 - Giri, Beny Candra, Agus Supardi, S.T., M.T (2016)
Power quality is very important thing in the Sugar Factory of Trangkil Pati. In the development of electricity in the Sugar Factory of Trangkil Pati, the power quality is decrease. The power quality problems is caused by the reduction of the power factor and harmonic distortion. Then, electric power quality analysis is done to solve the problems of decrease the power factor and harmonic distortion in the Sugar Factory of Trangkil Pati. The method used by modeling the electrical system on the Sugar Factory of Trangkil Pati using software ETAP 12.6. The simulation results of ETAP 12.6 software will be analyzed and used to determine the solution of power quality problems. Based on the simulation results it is needed to improve the power factor and to install harmonic filter at electrical system in the Sugar Factory of Trangkil Pati. Results of power factor by using capacitor banks is raising the effectiveness of electric power generated. The voltage drop also can be reduced from marginal condition becomes normal conditions. The installation of a harmonic filter can reduce harmonic distortion value on bus 36 and bus 49. On the bus 36 THDi value decreased by 27.01% from 43.76% to 16.75%, while THDv value decreased by 3.89% from 5.14% to 1.25%. For bus 49 THDi value decreased by 23.51% from 32.92% to 9.41%, while THDv value decreased by 3.76% from 4.81% to 1.05%.